A critical perspective on industry involvement in higher education learning: Enhancing graduates' knowledge and skills for job creation in Nigeria. Issue 1 (February 2021) - Okolie, Ugochukwu Chinonso; Nwajiuba, Chinyere Augusta; Eneje, Beatrice; Binuomote, Michael Olayinka; Ehiobuche, Christian; Hack-Polay, Dieu
This study explores how Nigerian higher education institutions can facilitate industry involvement in the design of programmes and activities that enhance the development of students' knowledge and skills for business start-ups, leading to job creation. Using interview and focus group methodologies, the researchers obtained rich information from 50 participants, including higher education teachers, final year undergraduate students who had taken part in the compulsory Student Industrial Work Experience Scheme and industry executives with an understanding of how industry can make a meaningful contribution to learning in higher education. Focusing on four dominant themes from the thematic analysis, the authors analyse the factors that contribute to students' knowledge and skill development. Building on human capital theory, they make recommendations for curriculum restructuring, renewed pedagogical approaches and competencies, building linkages between higher education and industry and career training and mentoring to enhance the development of students' knowledge and skills for job creation.